The millipede family Polydesmidae in the Caucasus (Diplopoda: Polydesmida) - Golovatch, Sergei; Evsyukov, Aleksandr; Reip, Hans (Zootaxa, 2016)
The family Polydesmidae is represented in the Caucasus by two genera and 11 species: Polydesmus abchasius Attems, 1898, P. lignaui Lohmander, 1936, P. muralewiczi Lohmander, 1936 and P. mediterraneus Daday, 1889 (all confined to the NW and W Caucasus, but of which only the former three are endemic to the region, whereas the latter species is an introduction), as well as Brachydesmus assimilis Lohmander, 1936 (endemic to most of the region, except Hyrcania), B. pigmentatus Attems, 1951 (= B. pereliae Golovatch, 1976, syn. n.) (subendemic to Hyrcania), B. superus Latzel, 1884 (a cosmopolitan introduction), B. furcatus Lohmander, 1936 (= B. furcatus exiguus Strasser, 1970, syn. n.) (endemic to the NW Caucasus), B. kalischewskyi Lignau, 1915 (= B. karawajewi Lohmander, 1928, = B. ferrugineus Lohmander, 1936, = B. talyschanus Lohmander, 1936, = B. bidentatus Golovatch, 1976, all syn. n.) (a highly polymorphous and widespread species, apparently in a stage of active speciation, subendemic to the entire region), B. kvavadzei sp. n., from Ajaria, Georgia, and B. simplex sp. n., from Abkhazia and Sochi, Krasnodar Province, Russia. All known Caucasian species of Polydesmidae are described in due detail, abundantly illustrated and keyed, and their distributions mapped.